2023
DOI: 10.3390/ijerph20032541
|View full text |Cite
|
Sign up to set email alerts
|

Homesickness at Home: A Scoping Review of Solastalgia Experiences in Australia

Abstract: Solastalgia is a term used to describe the pain and distress experienced by those witnessing their home environments destroyed or changed in unwelcome ways. Solastalgia is expected to become more prominent as climate change worsens and transforms landscapes. This scoping review examines and maps the existing literature on solastalgia in Australia, particularly focusing on Aboriginal and Torres Strait Islander experiences. Four focus questions guided the review to explore how solastalgia is conceptualized, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…As corroborated by the results provided by Breth-Petersen et al ( 22 ), an extensive search of the Pubmed, ProQuest, INFORMIT Indigenous, EBSCO, and Google Scholar databases determined that there was a significant gap in the literature that failed to include Aboriginal-specific discussion relating to solastalgia. Additionally, those in existence were primarily authored by non-Indigenous academics and were not reflective of a decolonised lens.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…As corroborated by the results provided by Breth-Petersen et al ( 22 ), an extensive search of the Pubmed, ProQuest, INFORMIT Indigenous, EBSCO, and Google Scholar databases determined that there was a significant gap in the literature that failed to include Aboriginal-specific discussion relating to solastalgia. Additionally, those in existence were primarily authored by non-Indigenous academics and were not reflective of a decolonised lens.…”
Section: Introductionmentioning
confidence: 82%
“…Thereby, the content was analysed and subsequently added to the review. Additionally, the literature review by Breth-Petersen et al ( 22 ) was identified and included in this final report as validation for conducting a decolonised, Indigenist scoping review process.…”
Section: Methodologies and Frameworkmentioning
confidence: 99%
See 3 more Smart Citations